Análisis jurídico y doctrinario de la sentencia No. 1849-10-JP/20 emitida por la Corte Constitucional sobre la discriminación a las mujeres en el contexto educativo por condición de embarazo - Tapia Sandoval, Maria Isabel (2024)
This research focuses on the legal and doctrinal analysis of sentence No. 1894-10JP/20 issued by the Constitutional Court of Ecuador, which addresses the complex problem of discrimination faced by pregnant women in the educational sphere, especially in police institutions. The main objective of this research is to examine the violation of the right to equality and non-discrimination experienced by pregnant women, exploring the various repercussions of this discrimination on their access to education and on the realization of their life projects within Ecuadorian society. To fully understand the context, a historical analysis of gender discrimination is carried out, highlighting its persistence, especially in the educational sphere. The research findings, supported by survey data and a thorough analysis of case law, strongly confirm the existence of discriminatory practices against pregnant women in police institutions, which negatively impacts their right to education and their personal development. The judgment under review stands as a fundamental reference for the protection of the rights of these women, marking a milestone in jurisprudence and establishing important precedents. In this context, as a result, specific recommendations are proposed. These include the revision of internal policies of the institutions, the implementation of awareness and training programs to promote cultural change, and the active promotion of legal measures that contribute to eradicating gender discrimination in the educational environment. The aim is to promote equal opportunities and guarantee an inclusive and respectful educational environment.